2003
DOI: 10.1046/j.1365-2648.2003.02786.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing staff mix models and outcomes

Abstract: Staff mix model was related to Registered Nurses' perceptions of the quality of patient care. It was also evident that other variables within the work environment might have more influence on the outcomes examined than the independent variable of staff mix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…These changes in LTC are reflected in our study results, where staff identified challenges with caring for complex residents but having little training and knowledge to do so. An appropriate mix of RNs, RPNs, and unregulated care providers is essential to ensure quality of care, particularly with respect to managing heart failure [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…These changes in LTC are reflected in our study results, where staff identified challenges with caring for complex residents but having little training and knowledge to do so. An appropriate mix of RNs, RPNs, and unregulated care providers is essential to ensure quality of care, particularly with respect to managing heart failure [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Non-traditional models may also include skill mix models (McGillis-Hall, 2003). These models are generated from studies that seek to measure staffi ng numbers as an indicator and measure of quality care (Castle & Engberg, 2007;Harrington, 2004;Harrington, 2005aHarrington, , 2005bHarrington, Kovner et al, 2000;Harrington, O'Meara, Collier, Schnelle, 2003;Harrington, Zimmerman, Karon, Robinson, & Beutel, 2000;Mueller & Karon, 2004;Mueller et al, 2006;Räikkönen, Perälä, & Kahanpää, 2007;Schnelle et al, 2004;Zhang et al, 2006).…”
Section: Models Of Care: Definitionmentioning
confidence: 99%
“…This is particularly so in aged care, where the shortage of nursing professionals is heavily felt amongst a client population with multiple, complex, comorbidities and increasing frailty (Australian C N C N C N C N workplace practice model; workforce staffi ng model; staffi ng model; nursing staff mix model; and model of care/care model/nursing care delivery system (Department of Health and Ageing, 2005;Kimball, Joynt, Cherner, & O'Neil, 2007;McGillis-Hall, 2003;McGillis-Hall & Doran, 2003;Wolf & Greenhouse, 2007). The terms 'models of care' and 'staffi ng models' are often used interchangeably and are rarely clearly defi ned within the literature, while 'workplace practice'; 'staffi ng models' and 'models of care' are very closely related and enmeshed with each other.…”
mentioning
confidence: 99%
“…In designing the survey instrument, the relevant writing in the service recovery performance literature (Mowday et al, 1979;Lucas et al, 1990;Parasuraman et al, 1990;Lytle et al, 1998;Yavas, 1998;Boshoff and Allen, 2000;Yoon et al, 2001;Babakus et al, 2003;Yavas et al, 2003) and the healthcare literature (Lytle et al, 1998;Rafferty et al, 2001;Budge et al, 2003;McGillis, 2003) were canvassed. Multiple item indicators were employed from this literature and adapted to operationalise the study constructs in the context of a healthcare setting.…”
Section: Measurementmentioning
confidence: 99%